2019
DOI: 10.1523/jneurosci.2663-18.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Differences between Dorsal Root and Trigeminal Ganglion Nociceptors in Mice Revealed by Translational Profiling

Abstract: Nociceptors located in the trigeminal ganglion (TG) and DRG are the primary sensors of damaging or potentially damaging stimuli for the head and body, respectively, and are key drivers of chronic pain states. While nociceptors in these two tissues show a high degree of functional similarity, there are important differences in their development lineages, their functional connections to the CNS, and recent genome-wide analyses of gene expression suggest that they possess some unique genomic signatures. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 63 publications
3
62
0
1
Order By: Relevance
“…Conversely, the trigeminal ganglion had RNAs encoding vasopressin, oxytocin and GABA receptor subunits. A similar RNAseq study focusing on RNAs being actively translated revealed that the trigeminal ganglion has greater expression of genes in the PI3K-mTORC1 pathway, while inhibitors of the pathway were more prominent in the dorsal root ganglion (Megat et al 2019). Enhanced expression of PI3K-mTORC1 pathway genes in the trigeminal ganglion was also confirmed at the protein level.…”
Section: Comparison Of Trigeminal and Dorsal Root Ganglia Sensory Neumentioning
confidence: 79%
“…Conversely, the trigeminal ganglion had RNAs encoding vasopressin, oxytocin and GABA receptor subunits. A similar RNAseq study focusing on RNAs being actively translated revealed that the trigeminal ganglion has greater expression of genes in the PI3K-mTORC1 pathway, while inhibitors of the pathway were more prominent in the dorsal root ganglion (Megat et al 2019). Enhanced expression of PI3K-mTORC1 pathway genes in the trigeminal ganglion was also confirmed at the protein level.…”
Section: Comparison Of Trigeminal and Dorsal Root Ganglia Sensory Neumentioning
confidence: 79%
“…We also observed non-labeled (WGA-488) cells and dead cells (propidium iodide, PI+), to be excluded from cell sorting and analysis ( Figure 2B). As expected, a significant number of viable small nociceptor cells were excluded in this analytical approach, to avoid including RNAs from non-nociceptor cells or attached fragments of dead cells (examples in Figure 2C; Thakur et al, 2014;Lopes et al, 2017;Megat et al, 2019).…”
Section: Confirmation Of Cell Population Specific Labeling Of Cutaneomentioning
confidence: 99%
“…To gain further insight into differentially regulated genes in our isolated population of neurons, we compared our dataset with similar studies on isolated DRGs from publicly available datasets which focused on nociceptors (expressing Na v 1.8) or DRG collected from the same lumbar spinal level (L2-L6; Figure 6; Thakur et al, 2014;Usoskin et al, 2015;Hu et al, 2016;Megat et al, 2019). Unsupervised hierarchical clustering of the top 260 genes revealed that a large number of genes display distinct patterns of expression dependent upon the technique used: isolated neurons from all DRG by translating ribosome affinity purification (TRAP) using the Na v 1.8 Cre mouse (Megat et al, 2019); single-cell isolation from L3 to L5 DRG (Hu et al, 2016); single-cell isolation from L4-L6 DRG (Usoskin et al, 2015); and magnetic cell sorting (MACS) using the Na v 1.8 TdTomato mouse (Thakur et al, 2014; Figure 6A). We found that, while our cutaneous nociceptor-enriched population clustered most closely with the datasets of both TRAP sorted and unsorted DRG from Megat et al (2019), our isolated population was characterized by its own unique dataset.…”
Section: Backlabeled Facs-sorted Cutaneous Cell Transcriptome Is Distmentioning
confidence: 99%
“…E-2-dependent connections between translational control of the Suppressor of Cytokine Signaling (SOCS) and mTOR phosphorylation (Augusto et al, 2010) or regulation of Rheb signaling (Pochynyuk et al, 2006) have been proposed (Matthews et al, 2005; Arbocco et al, 2016). These signaling pathways also play key roles in the excitability of nociceptors (Moy et al, 2017; Khoutorsky and Price, 2018; Megat et al, 2019b; Megat et al, 2019a) and may play a more prominent role in the maintenance of persistent nociceptor plasticity in females than males.…”
Section: Discussionmentioning
confidence: 99%